Uterine Artery Embolization Combined with Methotrexate in the Treatment of Cesarean Scar Pregnancy: Results of a Case Series and Review of the Literature - Zhang, Bo; Jiang, Zai-Bo; Huang, Ming-Sheng; Guan, Shou-Hai; Zhu, Kang-Shun; Qian, Jie-Sheng; Zhou, Bin; Li, Ming-An; Shan, Hong (Journal of vascular and interventional radiology, 2012)
To explore the clinical value of uterine artery embolization (UAE) combined with methotrexate in the treatment of cesarean scar pregnancy (CSP) before and after uterine curettage. From August 2009 to April 2012, 15 patients with CSP treated with UAE (before or after uterine curettage) were analyzed retrospectively. Eleven subjects with a definite diagnosis of CSP were offered preventive UAE combined with methotrexate before uterine curettage. The other four patients, who were misdiagnosed as having an intrauterine pregnancy, were treated with emergency UAE for uncontrollable massive hemorrhage after uterine curettage. Clinical data, treatment sequence, and outcome were analyzed, and a brief review of the published literature summarizing UAE in the treatment of CSP was performed. Eleven patients with definite CSP received preventive UAE combined with methotrexate followed by uterine curettage, and CSP was resolved successfully without hysterectomy. In the four misdiagnosed patients, three were treated successfully with emergency UAE. The other patient underwent uterine curettage and emergency UAE followed by repeat curettage, but hysterectomy was performed because of continued severe hemorrhage. Based on a small number of patients, it appears that UAE may be an effective means of treating CSP, including treatment in an emergency setting. Further study is required before the safety and effectiveness of UAE can be confirmed.